Panthera onca EN EL ÁREA DE CONSERVACIÓN REGIONAL CORDILLERA ESCALERA: UN NUEVO REGISTRO DE JAGUAR MELÁNICO EN LA SELVA TROPICAL DEL PERÚ - SAUCEDO-BAZALAR, Manuel Jesús (2023)
We present the first records of a melanistic jaguar (Panthera onca) coexisting with non-melanistic jaguars in the Cordillera Escalera - Regional Conservation Area, San Martín, Peru. Between the years 2017 and 2022, twelve camera traps were installed in a wildlife corridor to evaluate the occurrence of mammals and birds within the conservation area. A total record of 9 photos and 24 videos was obtained, of which 6 photos and 10 videos corresponded to a melanistic male specimen. The largest number of records was in April and July 2021, during night events. These results represent important evidence of the presence of previously undocumented melanistic jaguars in the area, allowing the strengthening of jaguar conservation initiatives and distribution evaluation within the Cordillera Escalera - RCA.